MANIFESTATIONS OF THE EPIDEMIC PROCESS IN SCARLET FEVER - Fakhriddinova Shakhnoza Fakhriddinovna (World Scientific Research Journal, 2025)
The disease is widespread but is more common in regions with temperate and cold climates. One of the characteristic features of scarlet fever is the periodic rise and fall in incidence rates. In addition to 2–4-year intervals, there are also larger time gaps (40–50 years) followed by a significant increase in the number of cases.In the early 1660s, T. Sydenham described scarlet fever as "an extremely insignificant ailment, barely worth mentioning." The clinical picture of scarlet fever at that time resembled that of the second half of the 20th century. However, just 15 years later, Sydenham encountered a severe form of scarlet fever and classified it alongside the plague in terms of severity. The 17th and 19th centuries were marked by alternating periods of mild and severe scarlet fever. Among well-known observations on this matter, F.F. Erisman noted: "There are periods of exclusively benign or only malignant epidemics of scarlet fever. The mortality rate in malignant epidemics is 13–18%, but it often rises to 25% and can reach even 30–40%."Due to an imperfect registration system and underdeveloped, often inaccessible medical care for the population, the official statistics of Tsarist Russia did not reflect the true level of scarlet fever incidence. However, data from the 20th century is extensive. Over a 100-year period, three large cycles of incidence were identified. By the end of the century, incidence rates had declined. The vast majority of patients were children; in Moscow, an average of 7,039 cases were recorded annually from 1996 to 2007, or 461.7 per 100,000 people. No significant trend changes were found across Russia, where an average of 224.9 children per 100,000 were affected annually. Between 1996 and 2007, a total of 716,193 cases of scarlet fever were recorded in Russia, with 64,743 cases in 2007 alone (86,004 cases in Moscow, including 6,590 in that year).